A New Perspective on the Ukrainian Refugee Crisis - Anders Åslund (CESifo Forum, 2022)
The Russian invasion of Ukraine has driven many people from their homes. Most of them are now seeking refuge in Europe. Fortunately, EU member states have learned from previous refugee crises: this time, they are willingly accepting people. For the first time, the EU has granted temporary protected status to all newly arriving Ukrainians. The European countries and the EU Commission are now working together to find efficient solutions and effective strategies to cope with the enormous challenges involved: UNHCR estimates that there will be nearly 8 million war refugees by June 2022. They need to be housed, they need healthcare, they need to be integrated into the education system and into the labor market. Currently, refugees are mainly concentrated in Eastern European countries. This entails additional costs for the respective governments. It is therefore of particular importance to find solutions for a fair distribution of the refugees and to share the financial burden among the EU member states. Ultimately, this orchestrated coordination will enable a better EU migration policy. In this issue of the CESifo Forum, our authors discuss how Europe can better and more efficiently address and solve all these challenges. The authors also provide helpful policy recommendations for national governments and for the EU.
Keywords: 330